Écrire l’histoire des migrations de travailleurs pauvres (Toscane, 13e-15e siècles) : historiographies et problèmes - Cédric Quertier (Cahiers d’histoire.)
Among internal migrations, those of the poor workers are massive but also very difficult to study. In fact, surviving records are more interested in goods than in persons, even if Tuscany is one of the most studied regions in Europe between 13th and 15th century. Both the richest and the poorest leave their village, but the later contribute to urban growth in the 13th-15th centuries, even if migrations among other rural areas take more importance afterwards. Poor workers from the countryside have to rent little houses on the outskirts of cities, they suffer from the lack of traditional bonds, but they can rely on institutional caritas. Often hired as salaried workers in the textile industry, whose condition is depreciated during the 14th century, they have to compete with itinerant and foreign workers. But relationship between status and economic condition must be deepened, because free work also means creation of new forms of exploitation, because, in the same time that citizenship becomes complex, crafters and workers are made stranger in their own society, and because links between social and geographical mobility are an open field of investigation.